Behavior Change Communication Strategy in Preventing Covid-19 in the Talise Community Health Center in Palu City - Herman; Firmansyah; Fikram; Mohammad Fikri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
At the end of 2019, the world was shocked by the outbreak of one of the new viruses, namely the new type of Corona (SARS-CoV-2) or Corona Virus Disease (COvid-19). This virus first appeared in Wuhan, a city in China. The World Health Organization WHO has declared Covid-19 a pandemic. Until now, almost all countries in the world have been infected with this virus. This study aimed To find out the risk communication system at Talise and to find out internal coordination with work partners in preventing Covid-19 in the Talise. Type of research used is qualitative, The approach used in this research is case study research which is used to examine an object or something that must be thoroughly and thoroughly researched. From the answers of the informants above, it shows that the risk communication system in preventing Covid-19 at PKM Talise has been divided into teams consisting of health promotion personnel, task force teams, and disease surveillance it was found that there are several parties who are partners in preventing covid, including the Police, Cadres, task force teams, and various NGOs that have programs that intersect with existing programs in PKM. Talise Health Center use many strategy to communicate with society. It’s hard in the beginning of pandemic, COvid-19 was new disease so Talise health center need time for find the best way to decrease the miscommunication or misinformation about Covid-19.